- #1

- 226

- 22

##G_{ii} = R_{ii} - \frac{1}{2}R##. But if ##G_{ii} = R_{ii} - \frac{1}{2}R## then that must mean that ##g_{ii} = 1##, which isn't necessarily true, as ##g_{ii} = a^2(\tau)##. Did he make a mistake?

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- I
- Thread starter JonnyG
- Start date

- #1

- 226

- 22

##G_{ii} = R_{ii} - \frac{1}{2}R##. But if ##G_{ii} = R_{ii} - \frac{1}{2}R## then that must mean that ##g_{ii} = 1##, which isn't necessarily true, as ##g_{ii} = a^2(\tau)##. Did he make a mistake?

- #2

haushofer

Science Advisor

- 2,492

- 883

- #3

- 226

- 22

Thanks. I was being sloppy.

- #4

haushofer

Science Advisor

- 2,492

- 883

Share: